The consequences of low water level in the Panama Canal and possible route alternatives: Comparing four routes through and around Panama from China to the US East Coast regarding emissions and time efficiency - Karlsson, Lisa; Jakobsson, Ella (My University, 2024)
In 2023, the area around central and eastern Pacific Ocean experienced one of its worst droughts known which resulted in reduced slots through the Panama Canal, consequently, ship owners had to consider optional routes instead of the Panama Canal. Therefore, the aim of the study is to identify alternative routes and analyze time efficiency and emissions created by each rote. Moreover, the aim is to identify the most suitable route regarding both emissions and time efficiency for 4 700 TEUs. The first scenario is based on the route Shanghai, China to Jacksonville, FL, US through the Panama Canal and turned out to be the most time efficient whilst having the second lowest release of emissions. The second scenario is based on the route Shanghai, China to Jacksonville, FL, US around the strait of Magellan and turned out to be the second least time efficient whilst having the highest release of emissions. The third scenario is based on the route Shanghai, China to Jacksonville, FL, US passing Panama by railroad and turned out to be the least time efficient whilst having the third highest release of emissions. The fourth scenario is based on Shanghai, China to Jacksonville, FL, US through Mexico by train and turned out to be the second most time efficient whilst having the lowest release of emissions. The study found functioning alternative routes through and around Panama, however, it was found difficult to compete with the Panama Canal especially regarding time efficiency. The study only focuses on containers and does not take emissions created whilst reloading into account, further the time and emissions created for port stops along the route has
Keywords: Panama Kanalen; CO2 utsläpp; sjöfart; tågtransport; intermodal; tidseffektivitet; CO2; Mexiko; USA; Panama Canal; emission; shipping; railway; intermodal; time efficiency; US